Comfort over safety: thermoregulation overshadows predation risk effects in the activity of a keystone prey. (18th December 2021) - Rocha, M.; Serronha, A.; Rodrigues, M.; Alves, P. C.; Monterroso, P.
Abstract: The activity level is a fundamental metric of animal behavior, related to the avoidance of predators, food acquisition, and thermoregulation. Animals need to weigh their activity budget to fulfill their energetic, social and reproductive requirements over the energetic costs of these activities. This task becomes further challenging for prey species, which also need to account for predation risk. To investigate the factors shaping proactive behavioral decisions leading prey species engagement in their diel activities, we implemented a multisite year‐round monitoring study on the Iberian rabbit ( Oryctolagus cuniculus algirus ), a key prey species in Mediterranean ecosystems. We deployed remotely triggered cameras over 15 sites to continuously monitor Iberian rabbits' activity. We estimated activity levels from time‐of‐detection data from camera traps, and modeled it as a function of climatic, intraspecific, predation, and resource‐related covariates. We found that Iberian rabbits exhibit a bimodal activity pattern peaking at sunrise and sunset, with a more pronounced peak occurring at sunrise during the nonbreeding season, and spend 9.15 ± 3.00 h/day (mean ± sd ) active. Diel activity levels were negatively affected by extreme environmental temperatures and density dependence, demonstrating the privileged importance of social interactions and normothermia maintenance. We found mammalian predator activity and abundance to have near‐negligible effects on the activity levels of this key prey, suggesting decreased antipredator behavior when risk is perceived as prolonged. Moreover, we argue that perceived risk may be more important than realized risk in shaping Iberian rabbits' activity level. These results provide valuable insights toward a comprehensive understanding of the factors underlying behavioral decisions made by prey species, relevant for maintaining their energetic and homeostatic balance. Abstract : Prey species weigh their activity budget to fulfill energetic, social, and reproductive requirements over the energetic costs of these activities while accounting for predation risk. We deployed remotely triggered cameras over 15 sites to continuously monitor Iberian rabbits' ( Oryctolagus cuniculus algirus ) activity, a multifunctional key prey species in Mediterranean ecosystems, and modeled it as a function of climatic, intraspecific, predation, and resource‐related covariates. Iberian rabbits exhibited a bimodal activity pattern peaking at sunrise and sunset and spend 9.15 ± 3.00 h/day active. Diel activity levels were negatively affected by extreme environmental temperatures and density dependence, demonstrating the privileged importance of social interactions and normothermia maintenance. Mammalian predator activity and abundance appeared to have near‐negligible effects on the activity levels of this key prey, suggesting decreased antipredator behavior when risk is perceived as prolonged.